Sistem Informasi Manajemen Aset dan Inventaris menggunakan QR Code di Kantor Camat Petang - I Kadek Subudi Setiawan; I Nyoman Yudi Anggara Wijaya (Jurnal IT UHB, 2020)
Abstract—Information and communication technology in this era it’s very rapid development. The impact of this information technology is very large felt in supporting the performance and activities ranging from schools, businesses and government agencies. Government agencies have used a lot of information systems that help the performance of these agencies to support the speed of the government process, but this information system has not been used as a whole in the government process especially in the sub-district office that still uses manual methods in recording inventory data owned by the agency. This research was made with the waterfall method that begins with the planning process of the system in which in this process a system of planning will be made related to the problems that exist in the camat petang office, then the modeling process where the system in the form of system design will be made, then the process is carried out implementation and testing of systems that have been made. Based on the problems and data obtained, an asset management information system and inventory were made using QR-Code, this system is useful for recording assets, providing information related to assets in a complete and fast way and providing convenience in bleaching items that are damaged or cannot be used anymore. Keywords: simanis, information systems, management, assets, inventory, QR-Code